2016
DOI: 10.1080/00365513.2016.1238504
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of serum squamous cell carcinoma antigen for hepatocellular carcinoma: a systematic review and meta-analysis

Abstract: The aim of this study was to ascertain the diagnostic value of serum squamous cell carcinoma antigen (SCCA) and SCCA-IgM for hepatocellular carcinoma (HCC). After a comprehensive search of PubMed and Web of Science databases, we identified eligible studies on the diagnostic value serum SCCAs for HCC. The quality of the eligible studies was assessed using the revised Quality Assessment for Studies of Diagnostic Accuracy (QUADAS-2) tool. The overall diagnostic value of SCCAs for HCC was pooled using a bivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…However, some unconventional roles were played in CSTMs: CEA and SCC-Ag were used for lung cancer diagnosis and prognosis [18,19]; CA125 and CA199 was reported as significant markers of endometrium pathology [20]; SCC-Ag had a fair diagnostic value for hepatocellular carcinoma [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, some unconventional roles were played in CSTMs: CEA and SCC-Ag were used for lung cancer diagnosis and prognosis [18,19]; CA125 and CA199 was reported as significant markers of endometrium pathology [20]; SCC-Ag had a fair diagnostic value for hepatocellular carcinoma [21].…”
Section: Discussionmentioning
confidence: 99%
“…The meta‐regression and subgroup analyses showed that the heterogeneity among the studies was related to patient selection, cut‐off values and the performance of tumour biopsies. In comparison to the previous studies, we performed a sensitivity analysis to achieve a higher level of reliability . The Giannelli et al study showed that the level of SCCA was inversely correlation with tumour size, which may be helpful in the early detection of HCC, and proposed a two‐step strategy with a combination of biomarkers to improve the diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous meta‐analysis included both English and Chinese language papers and compared the pooled diagnostic accuracies between SCCA and SCCA‐IgM; these data need to be updated . Several limitations of the most recent meta‐analysis include the following: (a) the data collection ended in September 2015; (b) the heterogeneity between studies was not explored; (c) one study published in 2012 by Biasiolo et al was omitted; (d) a study published by Crescenzi et al was included, but the recorded sensitivity of 51% and specificity of 49% might have been inappropriately extracted from the combination of AFP‐IgM and SCCA‐IgM; moreover, if one biomarker is insufficient to precisely diagnostic HCC, combinations of currently available biomarkers should be assessed by meta‐analysis; (e) to the best of our knowledge, the investigation of reasons for heterogeneity among studies beyond the computation of a single summary measure is an important purpose of meta‐analysis . Previous studies failed to assess heterogeneity because of the limited number of publications at the time.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some proteins specially expressed in HCC also have potential diagnostic value. Serum squamous cell carcinoma antigen (SCCA) has a moderate diagnostic value for HCC with pooled sensitivity of 0.61 and pooled specificity of 0.80 [ 45 ]. Osteopontin (OPN) shows a relatively high diagnostic accuracy for HCC with merged sensitivity of 0.86 and merged specificity of 0.86 [ 46 ].…”
Section: Discussionmentioning
confidence: 99%